Landscape of Post-Marketing Requirements Under the Pediatric Research Equity Act for Antibiotics from 2009–2024 - Daniel Selig; Funmi Aminu; Sue Cammarata; Ting Chen; Lauren Dolak; Stephen Duprez; Stephanie Ecker; Lisa Gault; Sandra George; Margaret Harkins; Clayton Litchmore; Michael Serenko; et al. (Antibiotics)
Background/Objectives: We reviewed Post-Marketing Requirements (PMRs) under the Pediatric Research Equity Act (PREA) for antibiotics approved in adults from 2009 to 2024 to better understand factors associated with PMR study completion. Methods: Initial PMRs, including study design and completion timelines were extracted from Food and Drug Administration (FDA) approval letters. Studies were cross-referenced at clinicaltrials.gov, with follow-up from adult approval to study completion or through 31 December 2024. Results: Eighteen antibiotics were approved in adults from 2009 to 2024, with 53 associated PREA PMRs. A total of nine PMRs were excluded from analysis (six exclusions for projected study completion dates on or after 12/31/2024, one exclusion due to lack of information, and two exclusions because the study type was not categorizable as Phase 1 or Phase 2). Of the 44 remaining PMRs in the analysis set, the median pediatric study follow-up time from adult approval was 5.3 years (range 0.94 to 11.5 years), with a study completion rate of 54.5% (N = 24). Small- and medium-sized companies had a study completion rate of 10% (N = 2/20) over a median of 6.44 years of follow-up, with no pediatric approvals. Large pharmaceutical corporations had a significantly higher study completion rate of 91.6% (N = 22/24; adjusted hazard ratio 20.3 95%CI, 5.02 to 82.4) over a median follow-up time of 4.7 years and achieved pediatric approval with labelling updates for 75% of antibiotics (N = 6/8). Conclusions: Compared to larger organizations, smaller pharmaceutical companies have experienced difficulty in PREA PMR antibiotic study completion, which may be related to financial difficulties in the challenging market for antibiotics. To improve PMR study completion, smaller companies require continued financial support and innovation in study design. For pediatric antibiotic development, the FDA accepts the extrapolation of efficacy from well-conducted randomized adult trials (i.e., pharmacokinetics (PK) and the safety approach). Therefore, sponsors should consider the use of single-arm, non-comparative PK and safety study designs to reduce the size and scope of trials. Sponsors should also assess whether the evaluation of an antibiotic is necessary in adolescents, or if data in a surrogate population of adults (e.g., low-weight adults) may serve as adequate evidence for adolescent approval.